(untitled) (Research, Society and Development, 2022)
The visibility of material reuse, subproducts and coproducts has been gaining more and more space in academical researches, industrial uses and innovation, therefore, the present study purpose are the possibilities of use of the sodium silicate solution from rice husk ash (RHA). In addition, Ionic Liquid (LI) and different ratios of silicon and niobium were added to seek improvements in the physicochemical properties of the elastomers. By means of X-Ray Diffraction (XRD) it was proved the obtaining of pure MCM-48 mesoporous material and, when employed varied molar ratios of Si/Nb, Nb-MCM-48. When applying in elastomers, concluded through maximum and minimum torque, great time and scorch, that the IL add and the MCM too caused effects in the performances, as scorch time acceleration and mechanical properties improvement.